CRABS CLAW Acts as a Bifunctional Transcription Factor in Flower Development - Gross, Thomas; Broholm, Suvi; Becker, Annette (Frontiers in Plant Science, 2018)
One of the crucial steps in the life cycle of angiosperms is the development of carpels. They are the most complex plant organs, harbor the seeds, and, after fertilization, develop into fruits and are thus an important ecological and economic trait. CRABS CLAW (CRC), a YABBY protein and putative transcription factor, is one of the major carpel developmental regulators in A. thaliana that includes a C2C2 zinc finger and a domain with similarities to an HMG box. CRC is involved in the regulation of processes such as carpel fusion and growth, floral meristem termination, and nectary formation. While its genetic interactions with other carpel development regulators are well described, its biochemical properties and molecular way of action remain unclear. We combined Bimolecular Fluorescence Complementation, Yeast Two-Hybrid, and Yeast One-Hybrid analyzes to shed light on the molecular biology of CRC. Our results showed that CRC dimerizes, also with other YABBY proteins, via the YABBY domain, and that its DNA binding is mainly cooperative and is mediated by the YABBY domain. Further, we identified that CRC is involved in floral meristem termination via transcriptional repression while it acts as a transcriptional activator in nectary development and carpel fusion and growth control. This work increases our understanding on how YABBY transcription factors interact with other proteins and how they regulate their targets.